Religiosity and Local Wisdom: Economic Security Strategy of Women of Indigenous Community - Hermi Oppier; Selvenco Tuasuun; Hendri Dony Hahury; Febryano Saptenno; Fredy Hendry Louhenapessy (Ridwan Institute, 2023)
This article highlights the meaning of ecclesiastical teachings based on the Bible as the Word of God in an effort to meet the needs of the poor in the Negeri (village) Booi congregation through the tradition or local wisdom of “nutmeg collecting”. This study employs Max Weber’s point of view on social action, where for every social activity carried out, there is always an internal motivation (Vertehen). This study was done in a qualitative manner with an ethnographic approach conducted in April 2022 – December 2022. The data was collected through in-depth interviews, observation and documentation. The data was analyzed following the stages proposed by Chariri with source triangulation as a strategy in examining the data validity. The results show that the local wisdom of “nutmeg collecting” could be used as a strategy in overcoming poverty problems, especially related to income inequality experienced by women. In the mainstream (classical/neoclassical) economic views, the behavior of this indigenous community was certainly very detrimental, as it was related to efforts to maximize income for oneself. However, on the contrary, this local wisdom also emphasized the needs of others which were supported by the religious teachings they believed in. This condition also emphasized that the presence of the local wisdom supported by the religious teachings was an informal insurance that the needs of the poor women of the indigenous community would always be met at any time through the availability of fallen nutmeg.